Small stories and accountability of discursive action in mediated political discourse: Contextualisation and recontextualisation of ordinary and not-so-ordinary participants - Fetzer, Anita (Frontiers in Communication, 2022)
This paper examines how participants in mediated political discourse use short narratives strategically to account for discursive action by contextualising and recontextualising their discursive selves, particular discursive acts and their intended and unintended perlocutionary effects. The data analysed are pre-election data (2017) and non-election data (2018), comprising online news reports from British broadsheets, parliamentary debates, political speeches from leading British politicians, and their web-based comments’ sections. The research is based on the differentiation between the generalised pragmatic premise and second-order theoretical construct of accountability2 of communicative action and its discourse-community-based particularisation, the first-order participant construct of accountability1. The discursive value of the latter is negotiated in context and in the political-discourse data further distinguished as regards accountability of and accountability for discursive acts. The analysis focuses on how ordinary and not-so-ordinary participants contextualise and recontextualise interfacing ordinary-life experience anchored in private domains and not-so-ordinary political action anchored in public and institutional domains. It considers (1) the production format comparing not-so-ordinary and ordinary story tellers; (2) stories with (a) not-so-ordinary, (b) ordinary, and (c) ordinary and not-so-ordinary characters; (3) ordinary settings and institutional settings; and (4) explicit and implicit evaluations by characters and tellers. The analysis shows that there is not only variation in the formatting of the short narratives with more-prototypical small stories and monolithic characters, settings and plot, and less-prototypical small stories with more dimensional characters, fuzzy settings and negotiated evaluations. There is also variation in the discursive function of the small stories: not-so-ordinary tellers and characters account for their discursive acts through life-world-experience-based accounts while at the same time implicating their leadership skills. They present themselves as listening to ordinary people, voicing their concerns in the public arena, initiating political action and acting on their behalf. Ordinary tellers and their ordinary characters tell their ordinary-life based stories, distancing themselves from the not-so-ordinary agents. In the mediated data, not-so-ordinary participants’ references to the private-public interface generally trigger conversational implicatures targeting sincerity, credibility and ideological coherence, while ordinary participants’ references to the private public interface are used to show the effects of political decision on their real-life experience.